Development of a J-T Micro Compressor. Issue 1 (November 2015) - Champagne, P; Olson, J R; Nast, T; Roth, E; Collaco, A; Kaldas, G; Saito, E; Loung, V
Abstract: Lockheed Martin has developed and tested a space-quality compressor capable of delivering closed-loop gas flow with a high pressure ratio, suitable for driving a Joule- Thomson cold head. The compressor is based on a traditional "Oxford style" dual-opposed piston compressor with linear drive motors and flexure-bearing clearance-seal technology for high reliability and long life. This J-T compressor retains the approximate size, weight, and cost of the ultra-compact, 200 gram Lockheed Martin Pulse Tube Micro Compressor, despite the addition of a flow-rectifying system to convert the AC pressure wave into a steady flow.